Continuous fluorescence assay for lecithin:cholesterol acyltransferase using a water-soluble phosphatidylcholine. - FS Bonelli; A Jonas (Journal of Lipid Research, 1992)
A water-soluble fluorescent phosphatidylcholine, 1,2-bis[4-(1-pyreno-butanoyl]-sn-glycero-3-phosphocholine (DPybPC) has been used to develop a sensitive, continuous assay for pure lecithin:cholesterol acyltransferase (LCAT) in solution. The monomeric substrate allowed us to examine the reaction of LCAT in the absence of a lipid/water interface in terms of the sensitivity of the enzymatic reaction to anions, ionic strength, apolipoproteins A-I and A-II, and a series of lysophosphatidylcholines and fatty acids. In contrast to the reaction of LCAT with aggregated phosphatidylcholines, the reaction of DPybPC with LCAT was not significantly affected by anions, ionic strength, nor apolipoproteins, indicating that these are only effectors of the interfacial reaction. Lysophosphatidylcholines and fatty acids inhibited LCAT in a chain-length-dependent manner below the critical micellar concentrations of these amphiphiles, indicating that the products of the LCAT reaction can bind to the enzyme and affect its kinetics even in the absence of an interface.